Environmental law in india - Gurdip Singh (Delhi, 2005)
This book projects the constitutional status of the right to healthy environment. The specialised legislations in India to prevent various forms of pollution are elaborated, analysed and evaluated in the book. The readership of the book includes students, teachers, researchers, legal practitioners, judges, NGOs dealing with environmental protection and all those interested in the study and acquisition of knowledge of environmental law.
Keywords: Environmental law-India